Global discovery of lupus genetic risk variant allelic enhancer activity - Xiaoming Lu (Nature Portfolio, 2021)
Thousands of genetic variants have been associated with lupus, but causal variants and mechanisms are unknown. Here, the authors combine a massively parallel reporter assay with genome-wide ChIP experiments to identify risk variants with allelic enhancer activity mediated through transcription factor binding.